Ecological niche modeling of pseudopaludicola motorzinho (anura, leptodactylidae), with two new distribution records and comments on its advertisment call variation - Cavalheri, Diego Gomiero [UNESP]; Ceron, Karoline; Carrillo, Juan F. C.; Neves, Matheus Oliveira; Santana, Diego Jose (Southwestern Association of Naturalists, 2024)
Species distribution is an essential factor in conservation efforts, and when new species are identified, a lack of information about their distribution may arise. In this study, we present an updated distribution map of Pseudopaludicola motorzinho, which includes two new occurrence records, and estimate the occurrence of the species using ecological niche modelling (ENM). The species was found in a total of 21 localities and occurs in four different ecoregions, namely Pantanal, Cerrado, Chiquitano Dry Forest, and Humid Chaco, located in the Midwest of Brazil and East Bolivia. The ENM predicted distribution remained adjusted to the occurrence points in Brazil and Bolivia, and projected the possible occurrence of the species in the eastern and central portions of Bolivia. The three advertisement calls that we recorded showed a slightly different pattern from those previously described for the species. Although P. motorzinho is present in other ecoregions, it is mainly associated with the Pantanal floodplains, with its life cycle intimately linked to the habitats provided by the floodplain. Unfortunately, this area has suffered severe drought and wildfires in the last years (2019-2022), which may have a direct impact on the species.